Co-infection of Chicken Layers With Histomonas meleagridis and Avian Pathogenic Escherichia coli Is Associated With Dysbiosis, Cecal Colonization and Translocation of the Bacteria From the Gut Lumen - Abdelhamid, Mohamed Kamal; Quijada, Narciso M.; Dzieciol, Monika; Hatfaludi, Tamas; Bilic, Ivana; Selberherr, Evelyne; Liebhart, Dieter; Hess, Claudia; Hess, Michael; Paudel, Surya (Frontiers in Microbiology, 2020)
Histomonosis in chickens often appears together with colibacillosis in the field. Thus, we have experimentally investigated consequences of the co-infection of birds with Histomonas meleagridis and avian pathogenic Escherichia coli (APEC) on the pathology, host microbiota and bacterial translocation from the gut. Commercial chicken layers were infected via oral and cloacal routes with lux-tagged APEC with or without H. meleagridis whereas negative controls were left uninfected. Except one birds, which died due to colibacillosis, no clinical signs were recorded in birds infected with bioluminescence lux gene tagged E. coli. In co-infected birds, depression and ruffled feathers were observed in 4 birds and average body weight gain significantly decreased. Typhlitis caused by H. meleagridis were present only in co-infected birds, which also had pronounced microscopic lesions in systemic organs such as liver, heart and spleen. The 16S rRNA gene amplicon sequencing showed that in co-infected birds, corresponding to the severity of caecal lesions, microbial species richness and diversity in caeca greatly decreased and the abundance of the Escherichia group, Helicobacter and Bacteriodes was relatively higher with a reduction of commensals. Most of the shared Amplicon Sequencing Variants between caecum and blood in co-infected birds belonged to Pseudomonas, Staphylococcus and members of Enterobacteriacae while those assigned as Lactobacillus and members of Ruminococcaceae and Lachnospiraceae were found mainly in negative controls. In infected birds, E. coli in the caecal lumen penetrated into deeper layers, a phenomenon noticed with higher incidence in the dead and co-infected birds. Furthermore, numbers of lux-tagged E. coli in caeca were significantly higher at every sampling date in co-infected birds. Altogether, infection of layers with H. meleagridis and E. coli resulted in more severe pathological changes, dramatic shift in the caecal mucosa-associated microbiota, higher tissue colonization of pathogenic bacteria such as avian pathogenic E. coli in the gut and increased penetration of E. coli from the caecal lumen towards peritoneum. The study provided novel insights into the parasite-bacteria interaction in vivo highlighting the role of H. meleagridis to support E. coli in the pathogenesis of colibacillosis in chickens.